COASTAL LAND UTILIZATION AS TOURISM ACCOMMODATION IN BULELENG - Ni Luh Supadmi Indrawati; I Nyoman Putu Budiartha; Luh Putu Sudini (NOTARIIL Jurnal Kenotariatan, 2018)
Abstract This research was conducted in Lovina Tourism Area. The problems raised in this thesis are: 1) how is the pattern of the control and use of coastal land for tourism accommodation in Lovina tourism area Buleleng regency? 2) What is the legal protection of coastal land rights used for tourism accommodation in the Lovina tourism area of Buleleng regency? And the finding in the field the acquisition of that the existing land in Lovina tourist area which is located in Kalibukbuk village, dominantly controlled by local community. This study belongs to empirical law study. In the case of the utilization of the lands possessed by the right ownership rights, there is also a leased to a third party. The technique used in collecting data required in this research is interview, observation and document. The result of the research is The development of tourism in the Lovina area of ​​Kalibukbuk Village as the center of the Tourism Area that directly and indirectly affects the economic, social and cultural life of the community, and developments are included in the control and utilization of land in coastal areas and There are two kinds of legal protection, namely preventive and repressive law protection: Protection of repressive law against customary land in Lovina area is a form of legal protection that is done related to the dispute faced by its citizens through the settlement in the judiciary, In the protection of preventive law, to ensure legal certainty of state land and management rights, registration shall be made, as described in the Minister of Home Affairs Regulation No. 1 of 1977, so that the Right to Own, Use and Use Rights may be issued. Keywords: Utilization; Coastal Land; Tourism Accommodation.